Modern Slavery in Supply Chains: an Analysis of Disclosure in the UK Banking Industry - ZHAO, Yilei (2020)
Purpose –The purpose of this dissertation is to examine how banks report on their efforts for eliminating modern slavery in their supply chain operations and to understand their approaches to disclosing information in response to the UK Modern Slavery Act 2015.